Association between Lifestyle Satisfaction and Tendency to Behavioral Change with Health Related Quality of Life among 40 Years Old and Over in (North of Iran) Mazandaran - RA Mohammadpour (علوم بهداشتی ایران)
Background and purpose: Health related quality of life (HQOL) has different dimensions and many factors affect it. The aim of this study was to investigate the association between lifestyle satisfaction and health- related quality of life in the population aged 40 year old and over. The question is, if there is not lifestyle satisfaction, how should be the pattern of tendency to behavioral changes? Materials and methods: This is a cross-sectional study. The statistical population is the inhabitants aged40 and over in Mazandaran province. One thousand and two hundred twenty five subjects by stratification and clustering random sampling were selected. The data were collected by face-to-face interview using the Persian version of the Short Form Health survey (SF-36). SF-36 is a standard questionnaire and Persian translation is valid and reliable. Lifestyle variable assessment includes smoking, physical activity, nutritional status, exercise and stress. Lifestyle satisfaction, tendency to behavioral change and demographic variables were assessed by separate questionnaire. The statistical analysis was performed by T-test and ANOVA by SPSS. Results: All health related quality of life components had meaningful relationship with lifestyle satisfaction. The mean of all the components of SF-36 measurements for those who had high lifestyle satisfaction were higher than the others (p<0.001).The highest amount of tendency to behavioral change was seen in nutritional status, exercise, stress control and smoking habits. Conclusion: According to the results, for promoting physical and mental health, lifestyle satisfaction must be increased. Nutrition, exercise, and giving up smoking are of great importance in physical health promotion.